Elucidation of the Algicidal Mechanism of the Marine Bacterium Pseudoruegeria sp. M32A2M Against the Harmful Alga Alexandrium catenella Based on Time-Course Transcriptome Analysis - Cho, Suhyung; Cho, Sang-Hyeok; Ko, So-Ra; Jeong, Yujin; Lee, Eunju; Jin, Sangrak; Jeong, Bo-Seong; Oh, Byung-Ha; Oh, Hee-Mock; Ahn, Chi-Yong; Cho, Byung-Kwan (Frontiers in Marine Science, 2021)
The marine dinoflagellate Alexandrium is associated with harmful algal blooms (HABs) worldwide, causing paralytic shellfish poisoning (PSP) in humans. We found that the marine bacterium Pseudoruegeria sp. M32A2M exhibits algicidal activity against Alexandrium catenella (Group I), inhibiting its motility and consequently inducing cell disruption after 24 h of co-culture. To understand the communication between the two organisms, we investigated the time-course cellular responses through genome-wide transcriptome analysis. Functional analysis of differentially expressed genes revealed that the core reactions of the photosystem in A. catenella were inhibited within 2 h, eventually downregulating the entire pathways of oxidative phosphorylation and carbon fixation, as well as associated metabolic pathways. Conversely, Pseudoruegeria upregulated its glycolysis, tricarboxylic acid cycle, and oxidative phosphorylation pathways. Also, the transporters for nutrients such as C3/C4 carbohydrates and peptides were highly upregulated, leading to the speculation that nutrients released by disrupted A. catenella cells affect the central metabolism of Pseudoruegeria. In addition, we analyzed the secondary metabolite-synthesizing clusters of Pseudoruegeria that were upregulated by co-culture, suggesting their potential roles in algicidal activity. Our time-course transcriptome analysis elucidates how A. catenella is affected by algicidal bacteria and how these bacteria obtain functional benefits through metabolic pathways.